PREFERENSI BERMUKIM MASYARAKAT PERBATASAN KOTA DAN KABUPATEN MALANG (DESA NGIJO KECAMATAN KARANGPLOSO) - Anisah Azizah; Turniningtyas Ayu R; I Nyoman Suluh Wijaya (Universitas Islam Sultan Agung Semarang, 2018)
ABSTRACT Development of city center encourages development in frontier city. Ngijo Village, one of frontier areas of Malang City and Malang Regency, was identified as expanding urban activity from Malang City which keep increasing from time to time, resulted in the rapid growth of settlements in the area. Increase of settlements in Ngijo village is growing rapidly, it is influenced by housing preference of residents. The method used in research is quantitative research with analytical technique used is the technique of conjoin analysis. Based on result of conjoint analysis, importance value in each attribute / variable is choice of housing unit with the importance value of 38,3%, environmental factor with importance value of 35,9%, accessibility with importance value of 14,3% and the last, choice of infrastructure with importance value of 11.5%. Choice of housing units to be the most dominant choice, while choice of infrastructure to be the lowest choice of living factors due to facilities and infrastructure available in the neighborhood of Ngijo Village is relatively low when compared with the city center.Keywords: housing preference, conjoin analysis ABSTRAKPerkembangan pusat kota mendorong terjadinya perkembangan di daerah perbatasan kota. Desa Ngijo salah satu kawasan perbatasan Kota Malang dan Kabupaten Malang, teridentifikasi terkena perluasan kegiatan perkotaan dari Kota Malang yang terus meningkat dari waktu ke waktu, yang mengakibatkan pertumbuhan permukiman yang cukup pesat pada kawasan tersebut. peningkatan permukiman pada Desa Ngijo semakin pesat, hal tersebut tentunya sangat dipengaruhi oleh preferensi bermukim dari masyarakatnya. Metode yang digunakan dapam penelitian merupakan penelitian kuantitatif dengan teknik analisis yang digunakan adalah teknik analisis konjoin. Berdasarkan hasil analisis konjoin nilai kepentingan pada masing-masing atribut/variabel adalah pilihan unit rumah dengan nilai kepentingan 38,3%, faktor lingkungan dengan nilai kepentingan 35,9%, aksesibilitas dengan nilai kepentingan 14,3% dan yang terakhir pilihan infrastruktur dengan nilai kepentingan 11,5%. Pilihan unit rumah menjadi pilihan yang paling dominan, sedangkan pilihan infrastruktur menjadi faktor pilihan bermukim yang paling rendah dikarenakan sarana dan prasarana yang tersedia di lingkungan permukiman Desa Ngijo tergolong rendah apabila dibandingkan dengan pusat kota.Kata kunci:preferensi bermukim, analisis konjoin